“Das ist nicht die Psychoanalyse”. Some Reflections on Freudian Definitions of Psychoanalysis: Theory, Practice and Politics - Scholten, Hernán (Revista de Humanidades de Valparaíso, 2023)
The question proposed in this dossier - what is psychoanalysis - has been asked many times over the decades, but perhaps only on a few occasions has it been the subject of a proper problematisation. This is compounded by the particular expression that is often heard in the psychoanalytic field, which is used as a mechanism of ostracism: “That’s not psychoanalysis!” Against this background, in the face of this apparent current lack of interest in definition, simultaneously with a certain urgency to point out what remains outside psychoanalysis, this brief article proposes to analyze a set of texts in which Freud seeks to delimit not only what psychoanalysis is but also the mechanisms involved and the authorized places to point out the deviations of the Freudian discipline. In other words, the aim here is to show that psychoanalysis, far from being reduced to a research methodology, a modality of treatment of neurosis and/or a theory, is also defined as a movement. And the question of the “ψ-movement” will lead to a reflection on its mechanisms of (re)production and some of its historical consequences. In the light of this journey, the aim is to show that this question, which in principle may seem merely technical and “scientific”, necessarily refers to the political.